Health Risk Assessment of Arsenic in the Drinking Water of Upper Sindh, Pakistan - Shar, N. U. H.; Shar, G. Q.; Shar, A. R.; Wassan, S. M.; Bhatti, Z. Q.; Ali, A. (Engineering, Technology & Applied Science Research, 2021)
Water is a valuable compound for plants, animals, and humans. Various contaminating agents pollute it, with arsenic being one of them. Measurements of arsenic in potable water in Upper Sindh were conducted during this study. The samples were prepared by microwave-assisted digestion and analyzed by an atomic absorption spectrophotometer. A total of 240 potable water samples were collected from 8 Talukas of Upper Sindh. DMS coordinates were also recorded with the help of the Global Positioning System (GPS). The highest arsenic content of 50µg/L was observed in Garhi Khairo Taluka. The average arsenic content in water samples of all of the Talukas, except Miro Khan, was found higher than the WHO permissible limit. The 69.2% of samples were found to be contaminated by arsenic. Therefore, the water of the studied area is concluded to be in poor condition for cooking and drinking.